Arquivos em performance: poéticas da memória na arte contemporânea - Renata de Alencar Ferreira (2017)
This research investigates the poetics of memory in contemporary artistic processes. A set of thirteen artworks stimulates reflections on the various figures of memory activation in art. Among them, the figure of the archive is highlighted, in the perspectives of Jacques Derrida and Michel Foucault. The archive configures a theoretical area that creates foundations for the understanding of other figures, such as: collection, bibliotheca, museum, catalog, creation documents, among other derivations. The object of study is approached according to a constellar methodology, inspired by the epistemological program of Walter Benjamin. The expression "archives in performance refers to the archives in the state of event, which are organized in an aesthetic plane, inaugurating poetics of memory. The analyzes allowed us to recognize some of the "occupations" of memory in the contemporary scene. We stand out: a distance from hegemonic memories, produce memories of forgetfulness and create a state of delay of the present time.